PENGARUH STATUS KEPEGAWAIAN DAN TINGKAT PENDIDIKAN TERHADAP KUALITAS KERJA PEGAWAI - A. Sufyan Pebrayetna (Holistik Manajemen: Jurnal Manajemen, 2022)
Employment status and education level are believed to affect the quality of work of employees in achieving the goals that have been set. The higher the employment status and education level, the higher the quality of work of employees in the company or organization. The purpose of this study was to analyze whether employment status and education level directly affect the quality of work of employees with the data analysis technique used is Path Analysis. In the results of simultaneous path coefficient testing, it was found that there was a significant effect between employment status and education level on the quality of work of employees. The magnitude of the influence of employment status and education level on the quality of work of employees simultaneously is 59.1%. These results can be interpreted that the higher the employment status and level of education, the quality of work of employees will increase. Keywords: Quality of Work, Employment Status, Education Level